Solve for the logarithmic equation above, assuming that is the golden ratio.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By the change of base rule, we can write the given equation as
lo g b ( a ) 1 = lo g b ( a ) + 1 ⟹ ( lo g b ( a ) ) 2 + lo g b ( a ) − 1 = 0 , and so lo g b ( a ) = 2 − 1 ± 5 .
With ϕ = 2 5 + 1 this implies that either lo g b ( a ) = ϕ − 1 or lo g b ( a ) = − ϕ ,
i.e., that either a = b ϕ − 1 or a = b ϕ 1 .